2018
DOI: 10.1021/acsnano.8b01353
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Growth Kinetics for the Formation of Uniform 1D Block Copolymer Nanoparticles by Living Crystallization-Driven Self-Assembly

Abstract: Living crystallization-driven self-assembly (CDSA) is a seeded growth method for crystallizable block copolymers (BCPs) and related amphiphiles in solution and has recently emerged as a highly promising and versatile route to uniform core-shell nanoparticles (micelles) with control of dimensions and architecture. However, the factors that influence the rate of nanoparticle growth have not been systematically studied. Using transmission electron microscopy, small- and wide-angle X-ray scattering, and super-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
108
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(121 citation statements)
references
References 105 publications
(192 reference statements)
12
108
1
Order By: Relevance
“…In this case, EtOAc was used as a selective solvent over a less polar solvent such as hexanes (which is typically used for PFDMS-b-PDMS self-assembly) as it is a good solvent for both the PMMA and PIP blocks. Self-assembly in EtOAc is typically slower than in less polar solvents such as hexanes as EtOAc is only moderately poor for the PFDMS core-forming block 67,68. PFDMS 52 -b-PDMS 414 seed micelles (block ratio 8.0 : 1.0, L n = 49 nm, L w /L n = 1.10) were prepared by sonication of a solution of long polydisperse micelles formed by self-nucleation in EtOAc for 2 h at 0 °C.…”
mentioning
confidence: 99%
“…In this case, EtOAc was used as a selective solvent over a less polar solvent such as hexanes (which is typically used for PFDMS-b-PDMS self-assembly) as it is a good solvent for both the PMMA and PIP blocks. Self-assembly in EtOAc is typically slower than in less polar solvents such as hexanes as EtOAc is only moderately poor for the PFDMS core-forming block 67,68. PFDMS 52 -b-PDMS 414 seed micelles (block ratio 8.0 : 1.0, L n = 49 nm, L w /L n = 1.10) were prepared by sonication of a solution of long polydisperse micelles formed by self-nucleation in EtOAc for 2 h at 0 °C.…”
mentioning
confidence: 99%
“…Boott et al recently reported a detailed study on the growth kinetics of a series of PFS‐ b ‐poly(dimethylsiloxane) (PFS‐ b ‐PDMS) BCPs . However, they found that, at all concentrations and over a series of different T c s, micelle growth did not fit Equation .…”
Section: Kinetics For Epitaxial Growth Of Unimers Onto Seed Micellesmentioning
confidence: 99%
“…Usually, altering T c and tuning solvency have a similar effect on the growth kinetics. At a higher T c or in a solvent with better solubility toward the core‐forming block, the exchange between the unimer and crystalline micelles is accelerated and the equilibrium shifts to dissolution, thus the growth rate of cylindrical crystalline micelles is reduced . Moreover, T c may also affect the width of the cylindrical micelles .…”
Section: Kinetics For Epitaxial Growth Of Unimers Onto Seed Micellesmentioning
confidence: 99%
See 2 more Smart Citations